1990
DOI: 10.1007/bf01963837
|View full text |Cite
|
Sign up to set email alerts
|

Results of screening for verocytotoxin-producingEscherichia coli in faeces in Belgium

Abstract: During an 18-month period all stools submitted to a microbiology laboratory in Belgium for culture were screened for Verocytotoxin-producing Escherichia coli (VTEC) serotype O157. In the stool samples from 3940 patients, eight (0.2%) VTEC O157 strains were isolated, seven of which were O157:H7. Additional screening for other serotypes of VTEC in 332 selected stool samples yielded four more strains (serotypes O2:K1:H6, O111:H-, O117:K1:H7 and O"C70/86":H-). The 0.3% isolation rate for all VTEC was comparable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
20
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 20 publications
8
20
0
1
Order By: Relevance
“…Although strains of O157 predominated, the proportion of non-O157 isolates (29.5%) among STEC in Palestine is similar to reported frequencies in Finland (20%) and Belgium (30%) [5,6]. The stx 1 and stx 2 genes were very frequent among O157 isolates from Palestine but there was a low frequency of hlyA and eaeA.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although strains of O157 predominated, the proportion of non-O157 isolates (29.5%) among STEC in Palestine is similar to reported frequencies in Finland (20%) and Belgium (30%) [5,6]. The stx 1 and stx 2 genes were very frequent among O157 isolates from Palestine but there was a low frequency of hlyA and eaeA.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, several strains of other serotypes have been implicated in both sporadic infections and outbreaks caused by STEC. In some studies, non-O157 strains have represented 20% [5] and 30% [6] of STEC isolated.…”
Section: Introductionmentioning
confidence: 99%
“…The isolates were identified as described before [12] by using classical biochemical tests. They were agglutinated with 0 1 5 7 antiserum and tested on the H7 antiserum-sorbitol fermentation medium [15].…”
Section: Characterization Of Vtec Isolatesmentioning
confidence: 99%
“…They are currently only recognizable by tests not currently used in diagnostic laboratories, such as VT production tests (cytotoxicity or ELISA) and molecular tests (DNA hybridisation or polymerase chain reaction, PCR)) [lo]. In a previous study [12] we found an isolation rate for 0 1 5 7 VTEC strains of 0.2% in the stools routinely submitted to our laboratory and we detected a few non-0157 strains by performing cytotoxicity tests on a limited number of samples. In this study we present the results of a large-scale screening using a PCR-based protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Em países como Chile (OJEDA et al, 1995), Argentina (LOPEZ et al, 1989) e Austrália (GOLDWATER & BETTELHEIM, 1994), STEC não-O157 são responsáveis pela maioria dos casos de SHU. Cepas STEC não-O157 têm sido frequentemente isoladas de pacientes com diarreia não-sanguinolenta (PIERARD et al, 1990;BROOKS et al,2005). Na literatura, já foram reportados isolamentos de STEC não-O157 em produtos de origem animal em diversos países (BOSILEVAC & KOOHMARAIE, 2011;FARROKH et al, 2013;MOHAMMED et al, 2014).…”
Section: Introductionunclassified